HUBUNGAN KEKUATAN CORE STABILITY DENGAN KESEIMBANGAN STATIS PADA LANSIA PANTI WERDHA BUDI MULIA 3 JAKARTA - Fajriani Zahra Zakiyah (2022)
Background:Aging is a natural process that occurs in every human being, because at this stage the body maintains the ability to regulate, the tissue will slowly decrease, at this stage of aging the body maintains its normal structure and function, and therefore this aging process affects infections. In this studi, the Core Stability measuring instrument in the form of sit ups and static balance used the one leg test. The purpose of this studi was to determine whether there was a relationship between Core Stability strength and static balance in the elderly at the Budi Mulia Nursing Home. 3. The research method used cross sectional research with descriptive correlative research design. The number of samples used in this studi were the elderly who were in Panti Werdha Budi Mulia 3 Jakarta, aged over 60 years with a total of 31 people. The results in this studi were measured using SPSS data with the Spearman correlation test with the results of sig (2-tailed) which was 942 . The conclusion of this studi is that there is no significant relationship between the strength of Core Stability and static balance in the elderly.